The fear / 3 - Higson, Charles, 1958- (Enemy, 2012)
In London, after a worldwide sickness infects adults, turning them into zombie-like creatures, DogNut and his crew embark on a deadly mission to find missing friends, as hungry, bloodthirsty grownups lie in wait.